Photophysical tuning of small-molecule-doped organic crystals with long-persistent luminescence by variation of dopants. (September 2021) - Song, Jiawei; Muleta, Desissa Yadeta; Feng, Wenhui; Song, Yakun; Zhou, Xueqin; Li, Wei; Wang, Lichang; Liu, Dongzhi; Wang, Tianyang; Hu, Wenping
Abstract: Design of host-guest structure has been an important direction in the development of organic long-persistent luminescence (LPL) materials, which have challenged traditional inorganic materials in some applications, such as anti-counterfeiting and bioimaging. The charge separation of donor-acceptor between host and guest is an effective way to induce LPL emission. Here, three crystalline materials were prepared by a convenient host-guest doping method at room temperature under ambient surrounding, i.e. in the presence of oxygen. Two kinds of crystals with long-lived charge separated states exhibited visible LPL emission with over 8 s and 6 s of duration. The persistent room-temperature phosphorescence effect caused by different generation efficiency of charge separated states was the main reason for the difference of LPL duration time. The crystal without charge separation had no LPL phenomenon because it was not a donor-acceptor system. This work indicates that the generation of charge separated states and their generation efficiency are the two key factors affecting the LPL properties and provides a new understanding for the design of organic LPL materials. Graphical abstract: Image 1 Highlights: Three crystalline materials with D-A architecture are prepared by a convenient doping method. Charge-separation can be directly related to the long-persistent luminescence (LPL). Generation efficiency of charge-separation can affect the LPL duration time.